Production potential and profitability of soybean [Glycine max (L.) Merill] as influenced by different production factors: PRODUCTION AND PROFITABILITY OF SOYBEAN AS INFLUENCED BY PRODUCTION FACTORS - A S KARLE; R V GITE; G S KHAZI; D N GOKHALE (Journal of Oilseeds Research, 2018)
A field experiment was conducted during kharif season 2015 to prioritize production factors and also suggest cost effective agronomic operation in soybean production. Adoption of whole package (T1) to soybean was significantly superior to all other treatments and produced highest gross monetary returns of ` 95104/ha and wasat par with treatment T4 (whole package-hoeing) (` 89689/ha) and T5 (whole package-plant protection) (` 84455/ha). Lowest gross monetary returns (` 38442/ha) of soybean was obtained in control treatment (T12).